2006
DOI: 10.1029/2006gl027933
|View full text |Cite
|
Sign up to set email alerts
|

Bottom water warming along the pathway of lower circumpolar deep water in the Pacific Ocean

Abstract: [1] Repeat trans-Pacific hydrographic observations along the pathway of Lower Circumpolar Deep Water (LCDW) reveal that bottom water has warmed by about 0.005 to 0.01°C in recent decades. The warming is probably not from direct heating of LCDW, but is manifest as a decrease of the coldest component of LCDW evident at each hydrographic section. This result is consistent with numerical model results of warming associated with decreased bottom water formation rates around Antarctica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 23 publications
5
49
0
Order By: Relevance
“…The Antarctic and North Atlantic limbs of the MOC appear to be of similar magnitude (e.g., Lumpkin and Speer 2007) Kawano et al 2006;Johnson et al 2007), and south Indian Oceans (e.g., Johnson et al 2008a) have all warmed over the last decade, indicating a change in the Antarctic contribution to the MOC. Furthermore, bottom waters close to Antarctica, at least in the Indian Ocean sector, also appear to have freshened (Rintoul 2007;Johnson et al 2008a), consistent with decadal time scale freshening in the source regions for this bottom water (Jacobs et al 2002).…”
Section: S62mentioning
confidence: 99%
“…The Antarctic and North Atlantic limbs of the MOC appear to be of similar magnitude (e.g., Lumpkin and Speer 2007) Kawano et al 2006;Johnson et al 2007), and south Indian Oceans (e.g., Johnson et al 2008a) have all warmed over the last decade, indicating a change in the Antarctic contribution to the MOC. Furthermore, bottom waters close to Antarctica, at least in the Indian Ocean sector, also appear to have freshened (Rintoul 2007;Johnson et al 2008a), consistent with decadal time scale freshening in the source regions for this bottom water (Jacobs et al 2002).…”
Section: S62mentioning
confidence: 99%
“…Assessing the sensitivity of AABW production and its contribution to the global thermohaline circulation is critical, because of the predicted impacts of a reduction/shutdown on the global climate system 5,6 . It is recently reported that the bottom layer of the North Pacific Ocean has been warming, possibly because of a slowdown of the Pacific meridional overturning circulation [7][8][9][10][11] . There is observational evidence that the overflows of DSWs formed off the Adélie and George V Land coast of East Antarctica predominantly supplies the bottom layer water in the Australian-Antarctic Basin 12,13 .…”
mentioning
confidence: 99%
“…Moreover, changes in these water properties are small enough in most regions that the higher accuracy of research ship observations is necessary for monitoring. The quasi-decadal repeats are now revealing increases in deep ocean temperature at almost all locations in the global ocean ( [106] and [107]). The changes are only relatively large in the vicinity (hundreds to thousands of kilometers) of the deep water sources, thus reflecting changes in ventilation properties -volume, temperature and density.…”
Section: Interior Ocean Beneath the Mixed Layermentioning
confidence: 99%